Análisis comparativo de los lenguajes de Programación Ionic y Xamarin orientados a entornos de desarrollo móvil. - Jacome Leal, Jorge Fernando (2023)
The present work analyzes that in the last periods of time web development has been in greater growth since every day more requests are made to the web to provide users with a better experience by making them use this medium, which is why we need better tools that allow fast, efficient and secure use of these applications, plus the ability to meet the needs of developers. Its purpose is a comparative analysis of the programming languages between developers that are ionic and xamarin oriented to mobile development environments, it is based on a specific analysis where inductive, analytical development is used, in addition the techniques of statistics, documentary for the collection of information related to the matter and its problems that exist at the moment of developing a solution, analyzing which of these two environments is the best, evaluating various criteria in order to find its best characteristics. Finally, we determined that Xamarin is an easy-to-use programming language for developers since it uses C# programming, however, the ionic programming language can develop hybrid applications based on web technology such as (HTML, CSS, JS).